CAMPUR KODE BAHASA DAERAH DAN BAHASA ASING KE DALAM PEMAKAIAN BAHASA INDONESIA DALAM PARODI INDONESIA LAWAK KLUB (ILK) - Sumariani, Ni Luh Gede (Humanis; Volume 10. No 1. Januari 2015)
The study is entitled “Code Mixing of Lokal and Foreign Languages in the Use of Indonesian in Indonesia Parody Comedy (ILK)”. There are three issues which will be analyzed in this study, namely the domains of language use, the types of code mixing, and the factors causing code mixing arising in Indonesia parody Comedy Club. The data collection use listening method, that is the data was gathered by listening to Indonesian parody video Comedy Club assisted with the technique of listening without speaking involvement and recording technique (making transcripts of the conversations). Sources of data in this study were derived from the data in the form of verbal descriptions of conversations between characters in Indonesian parody Comedy Clubs in the video which was aired from October 27 until December 29, 2013 which amounted to ten episodes. This study uses the theory of sociolinguistics ( code mixing, speech community, and bilingualsm). Based on the analysis, the findings were as follows: (1) in Indonesian parody Comedy Club, code mixing events occurred; (2) the types of code mixing found were inner code mixing, outer code mixing, and mixed code mixing; (3) code mixing was derived from Javanese, Sundanese, Bataknese, Jakarta Indonesian, English, Arabic, and Slang; (4) based on the linguistic elements, code mixing found was in tehe form of words, phrases, and clauses; and (5) the cause of code mixing in this parody was influenced by factors of roles, speakers, and languages.
Keywords: code mixing and sociolinguistic